Formation of gold nanoparticle dimers on silicon by sacrificial DNA origami technique. (1st November 2017) - Yamashita, Naoki; Ma, Zhipeng; Park, Seongsu; Kawai, Kentaro; Hirai, Yoshikazu; Tsuchiya, Toshiyuki; Tabata, Osamu
Abstract : To create a nanogap‐based device for single‐molecule label‐free detection using surface‐enhanced Raman spectroscopy (SERS), a new approach utilising DNA origami (DO) as a sacrificial nanostructure is proposed. In this approach, 15‐nm diameter gold nanoparticles (AuNPs) are precisely self‐assembled to form a dimer structure on opposite faces of a rectangular DO structure. The AuNPs are then fixed on a silicon chip supporting an amino‐terminated monolayer and the DO is selectively removed by vacuum ultraviolet (VUV) treatment followed by ultrapure water cleaning. X‐ray photoelectron spectroscopy measurements confirmed the successful removal of the DNA nanostructures and the VUV treatment had little effect on the diameter of the AuNPs. Quantitative evaluations showed that the original gap distance of about 3.8 nm was reduced to <2 nm after the DO structures were removed by the VUV treatment and ultrapure water rinse. The proposed technique can therefore be considered a simple and low‐cost alternative to EB lithography approaches.